Hexokinase and carnitine palmitoyltransferase activities in flight muscles of grasshopper Valanga nigricornis(burm.) - Lee, C. W.; Tan, C. H. (Pergamon Press, 1983)
1. The activities of hexokinase and carnitine palmitoyltransferase (CPT) activities were assayed in flight muscle mitochondria of Valanga nigricornis. 2. Kinetic analysis of the enzyme activities yielded the following information: for hexokinase, its Km (glucose) is 150 μM while its Vmax is 2.5 μmol/min/mg protein; the corresponding data for CPT are Km (palmitoylCoA) of 39 μM and Vmax of 22.2 nmol/min/mg mitochondrial protein. 3. Under conditions of equivalent rates of ATP production the hexokinase-CPT activity ratio is 64, suggesting that although V. nigricornis is a “mixed” fuel utilizer, it appears that carbohydrate oxidation constitutes the predominant energy source.